Sodium Nitroprusside Infusion for the Treatment of Schizophrenia. Issue 1 (21st September 2020) - Weiser, Mark; Zamora, Daisy; Levi, Linda; Matei, Valentin; Gonen, Ilan; Radu, Paull; Davidson, Michael; Davis, John M
Abstract: One previous small single-center clinical trial showed that a single intravenous administration of sodium nitroprusside added-on to antipsychotics improved a wide spectrum of schizophrenia (SCZ) symptoms more than placebo, and the improvement persisted for 4 weeks after infusion even though no additional drug was given. Our study attempted to replicate these data in a 4-week, add-on, double-blind, randomized, placebo-controlled trial on 20 patients performed in a site in Romania and a site in Moldova. This study's sample size and protocol were identical to the previous trial, including patients with a diagnosis of SCZ, within the first 5 years after diagnosis. Patients recruited needed to have a baseline total positive and negative syndrome scale (PANSS) score of 60 or above. Ten participants received a single dose of 0.5 µg/kg/min intravenous sodium nitroprusside over 4 hours, and 10 participants received matching placebo infusion, added-on to antipsychotics. The primary outcomes were the PANSS total score and the PANSS negative subscale. There were no significant between-group differences in PANSS total scores or negative subscale scores during the infusion on daily evaluations for the next 7 days nor on weekly evaluations at weeks 2, 3, and 4. No significant differences were found between the 2 study groups in adverse events. Meta-analyses including all 5 published randomized controlled trials on the topic, representing 155 subjects, do not show a statistically significant benefit of sodium nitroprusside. We conclude that the current evidence does not support the efficacy of sodium nitroprusside in the treatment of SCZ.